Administrativisation of punishment - Śliwiński, Emil (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The article describes the phenomenon of “administrativisation” of punishment. The legislator, when regulating an area of social relations, frequently chooses administrative monetary penalties instead of other instruments of repressive law, such as creating a crime or a petty offence. In particular the reasons for such a decision were analysed. On the basis of statutes adopted during last few years the character of the administrative monetary penalties was described. The possible directions of development of administrative liability in the context of system of law were also indicated.